The Influence Of Ability to Read The Al-Qur'an on Student Learning Results of Mathematics Program Unindra Jakarta - Nasution, Sumiah (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2021)
This article is the result of research to find out information about the ability and persistence of students in reading the Al-Qur'an and its effect on learning outcomes. The research method used was the f test and t-test and was analyzed with a simple linear regression statistical formula. This research was conducted on 46 students of the PGRI Indraprasta University, Jakarta Mathematics Education Study Program. Data collection techniques are observation, interviews, questionnaires, and oral and written tests. Based on the statistical analysis, it is concluded that the researcher's hypothesis data shows that it has been tested empirically that the ability to read the Qur'an influences student learning outcomes. This is indicated by the F-value> F table (106.726> 4.06), then Ho is rejected and Ha is accepted. Also indicated by the test t-value> t-table = (10.331> 2.01537). This means that there is a linear, positive and significant influence between the ability to read the Koran on student learning outcomes. The increase in student learning outcomes is influenced by the ability to read the Qur'an by 70.1%. The remaining student learning outcomes are influenced by factors not observed in this study amounting to 29.9%. This finding is a great opportunity for efforts to improve student achievement by guiding the ability to read the Koran that is official and sustainable. Concrete students need to be motivated to form Al-Qur'an (Halaqah) groups on campus whose activities can reach the Mathematics Education Study Program even by using online media. Lecturers should also provide rewards for students who are diligent and have good reading skills, let alone have a good talent for the Koran.